PENDAPAT GURU PENDIDIKAN JASMANI TERHADAP PEMBELAJARAN DARING PADA SMA NEGERI SE-KOTA PONTIANAK - Aprianto, M Reza; Triansyah, Andika; Bafadal, Muhammad Fachrurrozi; Sofyan, Davi (JOURNAL RESPECS (Research Physical Education and Sports), 2022)
This research is based on the impact of the covid-19 virus outbreak on education, one of which is physical education of sports and health which results in the learning process being conducted online. This study aims to find out the point of view or Perception of Physical Education Online Learning in High Schools in Pontianak City. This study uses quantitative descriptive method with survey research type, samples used in this study as many as 12 teachers from 8 schools, the analysis used in this study is validity test and reliability test. The result of this study is conducted validity test on 35 statements consisting of 4 indicators, there are 29 valid statement items and 6 invalid statement items with rhitung value > rtabel (0.334), followed by reliability test to see the questionnaire can be accepted or not to be conducted research then obtained a value of 0.783 which means the questionnaire is accepted. Thus, it can be concluded that the Perception of Physical Education to online learning in high schools in Pontianak, has a percentage of 63% which means it can facilitate or help.